Fermentative losses and chemical composition of elephant grass silage added with castor bean hull - Furtado, Rafael; Carneiro, Maria Socorro; Coutinho, Danielle; Cândido, Magno; Silva, Eranildo (Revista Ciência Agronômica, 2018)
Fermentation and chemical composition of elephant grass silage was evaluated with 0, 10, 20 and 30% castor been hull based on the natural matter. The experimental design was completely randomized with five replications. Silos were weighed out during manufacture, and reweighed before and after the opening after storage for 30 days. We determined the chemical composition, specific mass and effluent and gas losses, dry matter recovery, pH and ammonia nitrogen of the silage. The specific mass, pH, dry matter content, crude protein, acid detergent fiber, total carbohydrates and cellulose increased linearly (P